2019
DOI: 10.1080/10715762.2019.1632445
|View full text |Cite
|
Sign up to set email alerts
|

Whey proteins: targets of oxidation, or mediators of redox protection

Abstract: Bovine whey proteins are highly valued dairy ingredients. This is primarily due to their amino acid content, digestibility, bioactivities and their processing characteristics. One of the reported bioactivities of whey proteins is antioxidant activity. Numerous dietary intervention trials with humans and animals indicate that consumption of whey products can modulate redox biomarkers to reduce oxidative stress. This bioactivity has in part been assigned to whey peptides using a range of biochemical or cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 161 publications
0
20
0
1
Order By: Relevance
“…A number of previous studies also demonstrated an enzyme-dependent effect on the in vitro antioxidant potencies of WPHs. Mann et al [43] reported the antioxidant activity of WPHs generate using Flavourzyme, Alcalase or Corolase PP having TEAC values ranging from 0.81-1.42 µM TE/mg protein. They also suggested that the TEAC values of the WPHs were associated with the extent of hydrolysis which was also in agreement with the results of Salami et al [17] when hydrolysing whey proteins using Proteinase K, thermolysin, trypsin or chymotrypsin.…”
Section: In Vitro Antioxidant Propertiesmentioning
confidence: 99%
“…A number of previous studies also demonstrated an enzyme-dependent effect on the in vitro antioxidant potencies of WPHs. Mann et al [43] reported the antioxidant activity of WPHs generate using Flavourzyme, Alcalase or Corolase PP having TEAC values ranging from 0.81-1.42 µM TE/mg protein. They also suggested that the TEAC values of the WPHs were associated with the extent of hydrolysis which was also in agreement with the results of Salami et al [17] when hydrolysing whey proteins using Proteinase K, thermolysin, trypsin or chymotrypsin.…”
Section: In Vitro Antioxidant Propertiesmentioning
confidence: 99%
“…The increases in PV and TBARS with storage periods were observed (p<0.05). However, TBARS contents of both samples were below the rancidity limit of 1.0 mg MDA/kg sample [31]. The results indicated that an incorporation of RBO in carrageenan gel matrix prior to use in CFS production could potentially protect the autooxidation.…”
Section: Changes In Lipolysis and Lipid Oxidationmentioning
confidence: 85%
“…The oxidized proteins may further enhance the lipid oxidation. Giblin et al [31] reported that the content of protein carbonyls in milk and milk products significantly increased after heat treatment. However, TBARS contents of all samples were lower than the rancidity limit of 1.0 mg MDA/kg sample [32].…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…It is present in low quantities (<1%) in milk of most of the species [18]. It functions as an antioxidant and free radicals' scavenger as well as defend the organisms against infections and inflammations that can be attributed to its ability of iron sequester from the environment [19]. Besides its involvement in detoxification processes, its antineoplastic effect is important in inhibiting the attachment of tumor growth factors.…”
Section: Number Of Amino Acids/moleculesmentioning
confidence: 99%